'This loopy idea' an analysis of UKIP's social media discourse in relation to rurality and climate change. Issue 2 (3rd May 2016) - Reed, Matthew
Abstract : This paper focuses on the way that United Kingdom Independence Party (UKIP) attempted to communicate its policies and messages about the topic of renewable energy during 2013–2014. Renewable energy is a fruitful topic to consider as it has a strategic importance in the discussion of the future of the UK. The emergent theme from the analysis was not only rurality and renewable energy but the connection of the issue to scepticism about climate change. This paper uses the qualitative analyses the social media posts and a sample of the linked materials, with newspaper coverage, to reveal the key themes in the UKIP discourse.